The mechanism of endoplasmic reticulum (ER) stress in cell apoptosis and ROS (reactive oxygen species) of CNE2 cell line induced by single wall carbon nanohorn (SWCNH) - Cao, Xianbao; Gong, Shunmin; Chen, Shujin; Hu, Shuang; Li, Tianshu; Guan, Yanfei; Feng, Chun; Zhang, Jinqian (Frontiers in Materials, 2025)
IntroductionThe interaction between the materials themselves and cancer cells are rarely explored. Therefore, the biological roles of raw single wall carbon nanohorn (SWCNH) on endoplasmic reticulum (ER) stress in the apoptosis of CNE2 were explored.MethodsTherefore, ERS of CNE2 cells was induced by SWCNH, and 4-phenylbutyrate (4-PBA) was selected as a inhibitor of ERS. CNE2 cells were co-cultured with SWCNH, 4-PBA and SWCNH+4-PBA, respectively. Furthermore, the apoptotic status of CNE2 cells and its ROS (Reactive oxygen species) levels were determined. Moreover, the apoptotic protein expression of caspase 3 (cysteinyl aspartate specific proteinase 3), the expression levels of ER pathway protein eIF2α, ATF4 and CHOP, or the OS (Oxidative stress)-related proteins NQO1, GCLC, HO-1, and Nrf2 was detected, respectively.ResultsCNE2 apoptotic rate, ROS levels, the caspase 3 or ER pathway proteins ATF4 and CHOP expression, even the NQO1, GCLC, HO-1, and Nrf2 levels of oxidative stress-related proteins in the groups of SWCNH and SWCNH+4-PBA were higher compared to the control group. Moreover, these indicators were higher compared to the group of SWCNH+4-PBA (p < 0.05).DiscussionER stress is the key possible mechanism of CNE2 apoptosis induced by SWCNH. After injury of ERS, SWCNH causes oxidative stress injury, which may eventually lead to apoptosis of CNE2 cells.